2010
DOI: 10.1017/s0029665110003848
|View full text |Cite
|
Sign up to set email alerts
|

Murine models of premature ageing for the study of diet-induced immune changes: improvement of leucocyte functions in two strains of old prematurely ageing mice by dietary supplementation with sulphur-containing antioxidants

Abstract: Several immune functions are markers of health, biological age and predictors of longevity. A chronic oxidative and inflammatory state is the main cause of ageing and the immune system is involved in the rate of ageing. Thus, several murine models of premature ageing have been proposed owing to their early immunosenescence and oxidative stress, such as ovariectomised rats and mice, obese rats and anxious mice. In the last model, the most extensively studied by us, mice showing anxiety have an aged immune funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…We found that adult PAM exhibit an increase in oxidative stress possibly related to an altered bone remodeling. Moreover, the use of different kinds of antioxidants has been suggested to be a good alternative for preventing the age-related oxidative stress (De la Fuente and Miquel 2009;De la Fuente 2010) and the deleterious effects of oxidation in musculoskeletal system (Runge and Hunter 2006;Manolagas 2010). Thus, the present results indicate that adult PAM model can be a good candidate to proof the efficacy of antioxidant strategies to prevent age-related bone deterioration.…”
Section: Discussionsupporting
confidence: 51%
“…We found that adult PAM exhibit an increase in oxidative stress possibly related to an altered bone remodeling. Moreover, the use of different kinds of antioxidants has been suggested to be a good alternative for preventing the age-related oxidative stress (De la Fuente and Miquel 2009;De la Fuente 2010) and the deleterious effects of oxidation in musculoskeletal system (Runge and Hunter 2006;Manolagas 2010). Thus, the present results indicate that adult PAM model can be a good candidate to proof the efficacy of antioxidant strategies to prevent age-related bone deterioration.…”
Section: Discussionsupporting
confidence: 51%
“…The collection of peritoneal suspensions was at the adult (40±4 weeks; n=38), mature (56±4 wk; n=25), old (72±4 wk; n=15) and long-lived (96±4 wk; n=11) ages. Another group of animals were classified as prematurely aging mice (PAM) (n=10) and non-prematurely aging mice (NPAM) (n=10) according to their different behavior in a T-maze, as previously described [23, 24]. After their classification, the collection of the peritoneal suspensions was only at the adult age (40±4 wk).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, prematurely aging mice (PAM) are identified by their poor response in a simple T-maze test. These PAM at the adult age showed a premature immunosenescence that was accompanied by a shorter lifespan compared to their counterpart non prematurely aging mice (NPAM) of the same sex and chronological age [23, 24]. The second requirement can be confirmed in both humans (centenarians) and experimental animals such as extremely long-lived mice.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, when an animal shows a high-oxidative stress in its cells, these cells have an impaired function and that animal shows a decreased longevity (De la Fuente and Miquel 2009;Viveros et al 2007). This happens in chronologically and biologically older human subjects and mice, who show higher levels of inflammation and oxidative stress, that has been found to be related to higher morbidity and mortality in these aged individuals (Arranz et al 2010a;De la Fuente 2010). In contrast, subjects who achieve greater longevity, such as human centenarians and extremely long-lived mice, show in their immune cells a well-preserved redox state and functional response, which may be related to the ability of these subjects to reach a very advanced age in healthy condition (Alonso-Fernández and De la Fuente 2011; Alonso-Fernandez et al 2008;Arranz et al 2010a;De la Fuente 2010).…”
Section: Introductionmentioning
confidence: 99%